Is the COVID-19 disease associated with de novo nephritic syndrome? - Dheir,Hamad (2020)
SUMMARY INTRODUCTION: This study aims to determine the incidence of de novo nephritic syndrome (NS) in COVID-19 patients and identify its associated factors. METHODS: All ward patients with COVID-19 pneumonia were investigated. After determining the inclusion and exclusion criteria, the study population was identified. The urine dipstick test and urine protein creatinine ratio (UPCR) measurements were performed. Patients with de novo NS findings, nasopharyngeal swab, and urine RT-PCR tests were performed simultaneously RESULTS: This descriptive cross-sectional study was conducted with 21 patients with COVID-19. The mean age of the patients was 42.2±8.8 years, and 71.4% of them were male. The mean duration of follow-up was 28.4±9.3 days. The urine RT-PCR test was positive in one patient (4.8%). Improvements were observed in hematuria by 71.4%, and proteinuria by 85.7% at the end of the follow-up. A significant decrease in the measured UPCR was found in comparison to the baseline(P=0.000). Also, improvements were recorded in the complete blood counts, inflammatory parameters, ferritin, and coagulation tests, compared to the baseline. There was a positive correlation between baseline UPCR and ferritin, and a negative correlation between baseline UPCR and sodium values CONCLUSION: COVID-19-induced de novo nephritic syndrome may occur mainly due to tubulointerstitial involvement and often results in spontaneous remission. However, why these findings were not present in all patients who had no comorbidities is not clear.